Study of Electrical Parameter Calculation for Traction Network in Single-line Tunnel Based on the Extend of Carson Theory - DENG Yunchuan; GAO Hong; CHEN Jianjun (Kongzhi Yu Xinxi Jishu)
Carson theory assumes that all conductors on the earth take the ground as an unique loop circuit, but there are multiple return paths in one actual traction network, thus it is difficult to directly determine current distribution and obtain the current -carrying requirement of each conductor in traction network. Based on the loop circuit system of multi- conductor transmission, it revised the assumption of Carson theory and considered the conductors that actually involved in circumfluence. On the basis of this revised theory, it combined the equivalent depth calculation of the ground achieved by Tylavsky formula to complete comprehensive impedance parameter calculation of single-line tunnel, which explored new ways for the accurate description of mathematical model and the calculation of electrical parameters of the electrified railway traction network.